2000
DOI: 10.1101/gr.10.3.302
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Neuropeptide Y Receptor Family: Gene and Chromosome Duplications Deduced from the Cloning and Mapping of the Five Receptor Subtype Genes in Pig

Abstract: Neuropeptide Y (NPY) receptors mediate a variety of physiological responses including feeding and vasoconstriction. To investigate the evolutionary events that have generated this receptor family, we have sequenced and determined the chromosomal localizations of all five presently known mammalian NPY receptor subtype genes in the domestic pig, Sus scrofa (SSC). The orthologs of the Y 1 and Y 2 subtypes display high amino acid sequence identities between pig, human, and mouse (92%-94%), whereas the Y 4 , Y 5 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 59 publications
1
50
0
2
Order By: Relevance
“…Included among the 40 sequences were also two NPY-family receptors (on non-Hox chromosomes). These arose before the proposed chromosome duplications, although they still bind the same ligands (Wraith et al 2000). Other NPY-family receptors (Wraith et al 2000) as well as dopamine receptors D1 and D5 and adrenergic receptors support chromosome duplications, albeit a different paralogon than the one discussed here.…”
Section: G Protein-coupled Receptor-gprmentioning
confidence: 91%
See 1 more Smart Citation
“…Included among the 40 sequences were also two NPY-family receptors (on non-Hox chromosomes). These arose before the proposed chromosome duplications, although they still bind the same ligands (Wraith et al 2000). Other NPY-family receptors (Wraith et al 2000) as well as dopamine receptors D1 and D5 and adrenergic receptors support chromosome duplications, albeit a different paralogon than the one discussed here.…”
Section: G Protein-coupled Receptor-gprmentioning
confidence: 91%
“…These arose before the proposed chromosome duplications, although they still bind the same ligands (Wraith et al 2000). Other NPY-family receptors (Wraith et al 2000) as well as dopamine receptors D1 and D5 and adrenergic receptors support chromosome duplications, albeit a different paralogon than the one discussed here. Thus, the analysis performed by Hughes et al cannot be taken as evidence for or against block duplications.…”
Section: G Protein-coupled Receptor-gprmentioning
confidence: 91%
“…The comparative genomics and proteomics analysis has led to identification of biomarker by comparing it with already known human and mouse biomarker. It has been concluded that both the proteins are plasma membrane proteins and also both NPY1R and MC4R belongs to same familyof GPCR (Gprotein-coupled receptors) [19] [20], NPY1R bears greater similarity to MC4R in its domain organization. And both proteins are structurally and functionally similar.…”
Section: Resultsmentioning
confidence: 99%
“…Physiologically, the Y 4 R is involved in the regulation of food intake (9), colonic anion transport (10), and adipose tissue and bone formation synergistically with Y 2 R (11). The Y 4 R sequence is one of the least conserved members of the NPYR family among different species, making it the fastest evolving functional member of the family (12). This makes it difficult to transfer conclusions from other Y receptor members to this subtype.…”
mentioning
confidence: 99%
“…It is secreted after food ingestion in proportion to its caloric content (14), and it promotes appetite suppression and inhibition of gastric emptying (15). This ligand was already found in ancient tetrapod evolution and appears to be one of the fastest developing peptides of the family (12). Because of its role in appetite suppression, this system is a very attractive target for the design of new therapeutic compounds for fighting obesity.…”
mentioning
confidence: 99%